Roles of p53 in Various Biological Aspects of Hematopoietic Stem Cells. (20th June 2012) - Nii, Takenobu; Marumoto, Tomotoshi; Tani, Kenzaburo
Abstract : Hematopoietic stem cells (HSCs) have the capacity to self-renew as well as to differentiate into all blood cell types, and they can reconstitute hematopoiesis in recipients with bone marrow ablation. In addition, transplantation therapy using HSCs is widely performed for the treatment of various incurable diseases such as hematopoietic malignancies and congenital immunodeficiency disorders. For the safe and successful transplantation of HSCs, their genetic and epigenetic integrities need to be maintained properly. Therefore, understanding the molecular mechanisms that respond to various cellular stresses in HSCs is important. The tumor suppressor protein, p53, has been shown to play critical roles in maintenance of "cell integrity" under stress conditions by controlling its target genes that regulate cell cycle arrest, apoptosis, senescence, DNA repair, or changes in metabolism. In this paper, we summarize recent reports that describe various biological functions of HSCs and discuss the roles of p53 associated with them.